Planning – An Insights from Vidura Niti - C. Yogambal, C. Yogambal (Journal of Neonatal Surgery, 2025)
Vidura Niti is a great guide for management skills and also for organisational behaviour. Planning plays a vital role in all sorts of things like our day to day life. As in planning there are many types of planning which has special characteristics in it. As Vidura is a very skilled and talented person whose play a key role in epic Mahabharata. Planning is a step by step process it has steps to complete the plan vidura niti has 33 chapters through 40 of Udyoga Parva (the Book of Effort, is the 5 to18 books of the Indian epic Mahabharata).Viduraniti is also known as vidura statesman craft. There are many slokas which clearly explains about planning and the execution methods and how in those days have been planned. In the planning involves in the evolutions of the worlds. Vidura Niti - AI Vidura Niti, an ancient wisdom from the Mahabharata, offers timeless insights on strategic planning, ethical governance, and foresighted decision-making. Integrating AI with Vidura Niti principles can revolutionize modern leadership, crisis management, business strategy, and personal decision-making. The Vidura Niti Planning System leverages AI to develop a wisdom-backed, data-driven decision support framework.